Perancangan Dan Implementasi Sistem Informasi Customer Relationship Management (CRM) Berbasis Web Pada CV Anugerah Interindo - Ilham Sholahuddin; Farizi Ilham; Muhamad Farhan; Muhammad Fathan Antony (Router : Jurnal Teknik Informatika dan Terapan, 2026)
CV Anugerah Interindo is a company engaged in interior design, providing various products such as curtains, upholstery fabrics, and wallpaper. Currently, the company does not have a system to record and manage customer data in a structured manner. As a result, customer data management and interaction history are still handled manually, leading to difficulties in recording, searching for customer information, and monitoring the sales process. The purpose of this internship project is to design a web-based Customer Relationship Management (CRM) application to help the company manage customer data and sales processes more effectively. The development method used is the SDLC Waterfall model, which includes requirement analysis, design development, implementation using Laravel as the framework and MySQL as the database, testing, and maintenance. Data collection was conducted through observations and interviews with the company’s operational manager. The project scope includes eight main features: (1) customer contact management, (2) a Kanban-based sales pipeline, (3) activity management and follow-up scheduling, (4) customer interaction history, (5) quotation management, (6) sales reports, and (7) data export to Excel. The expected result is the development of a CRM system capable of storing and managing customer data, facilitating interaction recording, and helping monitor the progress of the sales process in a more structured manner.